Preparedness Tested: Severe Cerebral Malaria Presenting as a High-Risk Person Under Investigation for Ebola Virus Disease at a US Hospital. (8th August 2021) - Anesi, George L.; Meyer, Nuala J.; Reilly, John P.; Schweickert, William D.; Mikkelsen, Mark E.; Myers, Emma V.; Dickinson, Edward T.; Kelly, Matthew P.; Pegues, David A.; Fishman, Neil O.
ABSTRACT: In 2019, a 42-year-old African man who works as an Ebola virus disease (EVD) researcher traveled from the Democratic Republic of Congo (DRC), near an ongoing EVD epidemic, to Philadelphia and presented to the Hospital of the University of Pennsylvania Emergency Department with altered mental status, vomiting, diarrhea, and fever. He was classified as a "wet" person under investigation for EVD, and his arrival activated our hospital emergency management command center and bioresponse teams. He was found to be in septic shock with multisystem organ dysfunction, including circulatory dysfunction, encephalopathy, metabolic lactic acidosis, acute kidney injury, acute liver injury, and diffuse intravascular coagulation. Critical care was delivered within high-risk pathogen isolation in the ED and in our Special Treatment Unit until a diagnosis of severe cerebral malaria was confirmed and EVD was definitively excluded. This report discusses our experience activating a longitudinal preparedness program designed for rare, resource-intensive events at hospitals physically remote from any active epidemic but serving a high-volume international air travel port-of-entry.